A disintegrin and metalloproteinase domain 10 expression inhibition by the small molecules adenosine, cordycepin and N6, N6-dimethyladenosine and immune regulation in malignant cancers - Zhang, Wenqian; Fu, Jiewen; Du, Jiaman; Liu, Xiaoyan; Cheng, Jingliang; Wei, Chunli; Xu, Youhua; Fu, Junjiang (Frontiers in Immunology, 2024)
A disintegrin and metalloproteinase domain 10 (ADAM10), a member of the ADAM family, is a cellular surface protein with potential adhesion and protease / convertase functions. The expression regulations in cancers by natural products [adenosine (AD) and its analogs, cordycepin (CD), and N6, N6-dimethyladenosine (m62A)], and immune regulation are unclear. As results, AD, CD, and m62A inhibited ADAM10 expression in various cancer cell lines, indicating their roles in anti-cancer agents. Further molecular docking with ADAM10 protein found the binding energies of all docking groups were <-7 kcal/mol for all small-molecules (AD, CD and m62A), suggesting very good binding activities. In addition, analysis of the immunomodulatory roles in cancer showed that ADAM10 was negatively correlated with immunomodulatory genes such as CCL27, CCL14, CCL25, CXCR5, HLA-B, HLA-DOB1, LAG3, TNFRSF18, and TNFRSF4 in bladder urothelial carcinoma, thymoma, breast invasive carcinoma, TGCT, kidney renal papillary cell carcinoma, SKCM and thyroid carcinoma, indicating the immune-promoting roles for ADAM10. LAG3 mRNA levels were reduced by both AD and CD in vivo. ADAM10 is also negatively associated with tumor immunosuppression and interrelated with the immune infiltration of tumors. Overall, the present study determined ADAM10 expression by AD, CD and m62A, and in AD or CD/ADAM10/LAG3 signaling in cancers, and suggested a potential method for immunotherapy of cancers by targeting ADAM10 using the small molecules AD, CD and m62A.